2004
DOI: 10.1016/j.ab.2004.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Protein microarray technology and ultraviolet crosslinking combined with mass spectrometry for the analysis of protein–DNA interactions

Abstract: To gain insights into complex biological processes, such as transcription and replication, the analysis of protein-DNA interactions and the determination of their sequence requirements are of central importance. In this study, we probed protein microarray technology and ultraviolet crosslinking combined with mass spectrometry (MS) for their practicability to study protein-DNA interactions. We chose as a model system the well-characterized interaction of bacterial replication initiator DnaA with its cognate bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 37 publications
(60 reference statements)
1
19
0
Order By: Relevance
“…ACS, the rate-limiting enzyme of ethylene biosynthesis, has been described very recently as the first plant MAPK substrate in vivo (58). Liu et al (58) found that selected isoforms of ACS including ACS-6, which we identified in our study (Table II, number 16), are substrates of MPK6. Phosphorylation of ACS led to the accumulation of the protein and to ethylene production (58).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…ACS, the rate-limiting enzyme of ethylene biosynthesis, has been described very recently as the first plant MAPK substrate in vivo (58). Liu et al (58) found that selected isoforms of ACS including ACS-6, which we identified in our study (Table II, number 16), are substrates of MPK6. Phosphorylation of ACS led to the accumulation of the protein and to ethylene production (58).…”
Section: Discussionsupporting
confidence: 60%
“…Analytical protein microarrays consisting of antibodies or protein antigens are increasingly used to profile proteins or antibodies, respectively, in crude protein samples of interest (6,12). Using functional protein microarrays, proteins can be directly screened in vitro for a large variety of activities, including protein-protein (13,14), protein-DNA (15,16), protein-lipid (13), and protein-drug interactions (17,18), under a wide range of different conditions. Furthermore previous studies have demonstrated the suitability of protein microarrays to study protein phosphorylation by kinases, however, only in a low or medium throughput manner (17,19,20).…”
Section: Molecular and Cellular Proteomics 4:1558 -1568 2005mentioning
confidence: 99%
“…The possible adverse e¡ects of spot-to-spot variability, for example, has been controlled by replicate spotting of the same analytical reagent, using four or 16 replicates. 86,87 A more signi¢cant challenge to the use of protein microarrays or other highly multiplexed assays in the clinical laboratory is that conventional procedures for daily QC of quantitative assays are likely to be impracticable for many microarray assay formats. In particular, the practice of running high-and low-range controls for each analyte becomes unwieldy when hundreds of analytes are involved.…”
Section: Quality Controlmentioning
confidence: 99%
“…4, C and D). In FBP, the peptides RKARGT-GELTQLLNS (aa [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] and GTIFGIYRKKSTDEP (aa 130 -147) were detected by overlay screens (Fig. 4, C and D).…”
Section: Fig 2-continuedmentioning
confidence: 99%